Effect of Variations in the Composition of Cow's Rumen and Straw on the Quality of Organic Fertilizer - Sugito, Sugito; Al Kholif, Muhammad; Ratnawati, Rhenny; Permatasari, Nidya (BERKALA SAINSTEK, 2023)
Organic fertilizer raw materials that can be obtained naturally and are rich in fertilizer nutrients can be found in animal slaughtering activities. Slaughtering activities generally produce animal waste and manure, which can be used as raw material for organic fertilizer. This study aimed to investigate the effect of the composition of raw materials on the quality of organic fertilizers. The organic fertilizer parameters studied were C/N, P, K, pH, and temperature. This study used four reactors with each reactor volume of 120 L and the exact weight of raw materials in each reactor of 20 kg. Variations in the composition of the raw material of the rumen of Madura cattle and straw in this study were RK (100% cow rumen), R1: (65% cow rumen: 35% straw), R2: (50% cow rumen: 50% straw), R3: (35% cow rumen: 65% straw). The composting process is carried out for 50 days. Analysis of the quality parameters of organic fertilizer using SNI 2803: 2010. The results showed that differences in the content of the raw materials impacted the quality of the generated organic fertilizer. R3 (35% rumen cattle: 65% straw) with C/N ratio = 13.25, P = 6.12%, K = 7.55%, pH = 6.82, and Temperature = 33.7oC are variations in the raw material composition for Madura cattle rumen and straw that fulfill the quality criteria of the Regulation of the Minister of Agriculture Number 70 of 2011.